EFEKTIVITAS SPORT EDUCATION MODEL TERHADAP PENGETAHUAN PERMAINAN SEPAK BOLA SISWA SD NEGERI 7 DESA SALOAN DOLOK KECAMATAN RONGGUR NIHUTA SAMOSIR - Manalu, Rizki Bastanta Boang; Nainggolan, Aser Paul; Sitepu, Brema Maklorin (JURNAL CURERE, 2023)
This research was motivated by students' lack of awareness of their motivation in learning using the sports education paradigm, resulting in ineffective interactions with peers. In contrast to sports in general where students only act as players, the sports education model requires students to play various roles. Students learn to become coaches, referees and scorekeepers as well as athletes in the sports education paradigm. The aim of this research is to find out how students at SD Negeri 7 Saloan Dolok Village, Ronggur Nihuta Samosir District feel about football. One of the problems with school observations is that PJOK teachers are not familiar with football content when implementing the autonomous curriculum. This research is a quantitative descriptive study that uses survey methodology and pretest and posttest data collection procedures in the form of a questionnaire. The population of this study consisted of 20 students. Quantitative descriptive analysis strategies are presented in percentage form in data analysis techniques. The results of the research showed that the results of class V students' interest in learning football in the sports education model at SD Negeri 7 Saloan Dolok Village, Ronggur Nihuta Samosir District were obtained by 13 students (65%), very interested, even 4 students (20%) were interested. Interest: 2 students (10%) were quite interested, 1 student (5%) was less interested. Based on the conclusions of this research, it is recommended that teachers better understand the independent curriculum to achieve learning goals and increase students' interest in being involved in learning.